Anti-Americanism in Contemporary Indonesia - Saiful Mujani (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2005)
This paper attempts to explore these two basic arguments. To that end we need first to discuss what is meant by